Rancang Bangun Sistem Informasi Stok Barang Menggunakan Metode Prototype Berbasis Web di CV. Mulia Jawa Logam - Maulana, Lucky; Sukisno; Sofyan, Asep Abdul (Jurnal Ilmiah Fakultas Teknik, 2025)
This research aims to develop a Stock Inventory Information System using the Prototype method based on the web at CV. Mulya Jaya Logam. The development method used is the Prototype method, which allows the creation of a system prototype that can be tested and iteratively developed according to user needs. This information system is designed to assist CV. Mulya Jaya Logam in managing their stock inventory more efficiently. In this study, a requirements analysis phase was conducted by collecting data from CV. Mulya Jaya Logam to understand their business processes related to stock inventory. Based on this analysis, a prototype system was designed, including a web-based interface and features that cater to user needs. Subsequently, the prototype system was implemented using web technologies.The results of this research include a web-based Stock Inventory Information System that has been tested and evaluated by users from CV. Mulya Jaya Logam. This system provides convenience in recording and monitoring stock inventory, thereby assisting the company in optimizing their stock management. It is hoped that this system can be an effective solution in addressing stock inventory issues at CV. Mulya Jaya Logam.